Peran Strategis Akademisi dalam Mendorong Inovasi Pelayanan Kesehatan Melalui Lomba Inovasi Daerah (LINDA) Kabupaten Cilacap Tahun 2025 - Lina Puspitasari; Yenni Kristiana; Adi Kurniawan (Jurnal Pengabdian Ilmu Kesehatan, 2025)
This article presents a critical analysis of the role of academics as judges in the 2025 Cilacap Regency Regional Innovation Competition (LINDA), focusing on the health sector. The study details the judging mechanism, which took place in two stages: an administrative selection to ensure completeness and suitability of documents, and a presentation assessment that explored the innovations' substance, sustainability, and potential for replication. Field observations revealed a wide variety of proposed innovations, ranging from the use of information technology for health services, village health cadre empowerment programs, to cross-sector partnership models. These innovations have been shown to have a significant impact on service efficiency, increased access, and strengthened community participation in maintaining health. However, various challenges remain, including limited competent human resources, minimal sustainable funding, and suboptimal supporting information systems. This analysis places these innovations within the framework of national innovation policy and compares them with good practices from case studies such as PUSTAKA and Mobile JKN, which serve as references for measuring the relevance, scalability, and sustainability of innovations at the regional level. The jury's role is positioned not merely as an assessor, but also as a mentor, facilitator, and validator of science-based innovative solutions. The involvement of academics in this process is a form of community service that has a direct impact on improving the quality of public policy, while strengthening the culture of innovation within local government. The findings of this study confirm that the active involvement of the jury can provide valuable empirical input for formulating strategies for developing regional health innovations.